The Order of Hypersubstitutions of Type (2,1) - Tawhat Changphas; Wonlop Hemvong (International Journal of Mathematics and Mathematical Sciences)
Hypersubstitutions are mappings which map operation symbols to terms of the corresponding arities. They were introduced as a way of making precise the concept of a hyperidentity and generalizations to 𝑀-hyperidentities. A variety in which every identity is satisfied as a hyperidentity is called solid. If every identity is an 𝑀-hyperidentity for a subset 𝑀 of the set of all hypersubstitutions, the variety is called 𝑀-solid. There is a Galois connection between monoids of hypersubstitutions and sublattices of the lattice of all varieties of algebras of a given type. Therefore, it is interesting and useful to know how semigroup or monoid properties of monoids of hypersubstitutions transfer under this Galois connection to properties of the corresponding lattices of 𝑀-solid varieties. In this paper, we study the order of each hypersubstitution of type (2,1), that is, the order of the cyclic subsemigroup of the monoid of all hypersubstitutions of type (2,1) generated by that hypersubstitution.